Antitumor activity of low-dimensional alumina structures; AIP Conference Proceedings; Vol. 1760 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications 2016 - Korovin M. S. Matvey Sergeevich (2016, 2016)
Title screen